DOZ047.20: Growth, feeding difficulties, and developmental scores in children born with esophageal atresia: a single-center study. (24th June 2019) - Grech, A; Kwan, M; Hatton, L; Robinson, P; Karpelowsky, J; Collin, M; Tzannes, G; North, H; Fitzgerald, D A
Abstract: Background: Children with repaired tracheoesophageal fistula/oesophageal atresia (TOF/OA) often have ongoing feeding difficulties and poor growth related to esophageal dysmotility, strictures, gastroesophageal reflux, aspiration, and respiratory infections. The impact of neurocognitive development on feeding in this cohort is less well studied. Objective: The objective of this study was to investigate the growth, parent-reported feeding difficulties, and developmental scores of children with TOF/OA at The Children's Hospital at Westmead in Sydney, Australia. Methods: The validated Montreal Children's Hospital Feeding Scale (MCH-FS) was completed by parents of patients aged 6 months to 6 years at a multidisciplinary aerodigestive clinic between February 2016 and October 2018. Growth, developmental outcomes (using the Bayley Scales of Infant and Toddler Development [BAYLEY-III]), demographic information, OA subtype, and associated comorbidities were reviewed. Results: Forty-three caregivers completed the MCH-FS at least once, with questionnaires returned up to five times, totaling 101 reviews. The mean age was 4 years (± 1.9) and 53% were female. Thirty percent of patients were born prematurely and 30% had VACTERL association. Mean [± SD] growth z -scores were below WHO/CDC means for weight (−0.86 ± 1.37), length/height (−0.70 ± 1.2), and weight-for-length/BMI (−0.35 ± 1.15). BAYLEY-III scores were available for 27 children at 13 (± 1) months. Mean scores for four domains were within 'average' range (8–12): cognition (11 ± 2), receptive language (8 ± 3), expressive language (8 ± 2), and fine motor skills (9 ± 2). The mean gross motor score was below average (7 ± 3). Parent-reported feeding difficulties were moderate. When first completed, cumulative MCH-FS scores indicated 44% of patients had severe feeding difficulties, 40% moderate, and 14% mild. Sixty percent of patients required referral to a speech pathologist. However, most parents did not feel that these feeding difficulties influenced the relationship with their child or their family (88% and 84%, respectively). Conclusions: The majority of patients in the cohort experienced significant feeding difficulties and some below average developmental scores, underscoring the need for multidiscplinary support for children born with TOF/OA. Further work in correlating growth, developmental, and feeding outcomes within subjects will assist in identifying early risk factors that may highlight infants most predisposed to these challenges, and who may benefit from early intervention.